SABAR DALAM MENGHADAPI PERMASALAHAN DALAM PERSPEKTIF HADIST NABI SAW - Nanda Inka Fitri; Zahara; Ainul Gani; Guntur Cahaya Kesuma; Amirudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to explore the concept of patience (sabr) in facing life's challenges from the perspective of the hadith of the Prophet Muhammad SAW. The focus of this study is to analyze the various forms of problems faced by individuals and the solutions of patience recommended in the hadith. The methodology employed is qualitative research with a library research approach, which includes textual analysis of hadith from primary sources such as Sahih al-Bukhari and Sahih Muslim, as well as related literature. The findings indicate that patience is not merely a passive attitude, but rather a manifestation of faith and inner strength. The Prophet SAW teaches that patience in the face of calamities, emotional pressures, and social conflicts is key to achieving tranquility and drawing closer to Allah. This finding emphasizes the relevance of the values of patience in the context of modern life, particularly in overcoming stress, strengthening social relationships, and supporting spiritual resilience. The implications of this research highlight the importance of internalizing the value of patience in the education and daily lives of Muslims. The novelty of this study lies in its comprehensive approach that connects the hadith on patience with contemporary challenges, while also providing practical guidance for individuals in facing life's trials.